(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Distance learning is a learning system that does not take place in one room and there is no face-to-face interaction between the teacher and the learner. This study aims to determine the impact of implementing distance learning in Indonesia from a commognitive point of view. This research is a descriptive type of research with a total of 543 participants who come from high school students in Pasuruan district, Indonesia. Data collection using a questionnaire. After the questionnaire is collected, it is analyzed using the Miles and Huberman method through reduction, display data, and conclusion, then it will be studied based on the commognitive theory. The results show that based on commognitive studies, students are more likely to still need a visual mediator as a visible object to be used as a communication medium, its realization depends on the material context. Students need to communicate to ask questions related to material that has not been understood. So it can be said that visual mediator is important during distance learning.